Differential role of STIM1 and STIM2 during transient inward (T(in)) current generation and the maturation process in the Xenopus oocyte - Serrano-Flores, Barbara (BMC Physiol, 2014)
BACKGROUND: The Xenopus oocyte is a useful cell model to study Ca(2+) homeostasis and cell cycle regulation, two highly interrelated processes. Here, we used antisense oligonucleotides to investigate the role in the oocyte of stromal interaction molecule (STIM) proteins that are fundamental elements of the store-operated calcium-entry (SOCE) phenomenon, as they are both sensors for Ca(2+) concentration in the intracellular reservoirs as well as activators of the membrane channels that allow Ca(2+) influx. RESULTS: Endogenous STIM1 and STIM2 expression was demonstrated, and their synthesis was knocked down 48–72 h after injecting oocytes with specific antisense sequences. Selective elimination of their mRNA and protein expression was confirmed by PCR and Western blot analysis, and we then evaluated the effect of their absence on two endogenous responses: the opening of SOC channels elicited by G protein-coupled receptor (GPCR)-activated Ca(2+) release, and the process of maturation stimulated by progesterone. Activation of SOC channels was monitored electrically by measuring the T(in) response, a Ca(2+)-influx-dependent Cl(−) current, while maturation was assessed by germinal vesicle breakdown (GVBD) scoring and electrophysiology. CONCLUSIONS: It was found that STIM2, but not STIM1, was essential in both responses, and T(in) currents and GVBD were strongly reduced or eliminated in cells devoid of STIM2; STIM1 knockdown had no effect on the maturation process, but it reduced the T(in) response by 15 to 70%. Thus, the endogenous SOCE response in Xenopus oocytes depended mainly on STIM2, and its expression was necessary for entry into meiosis induced by progesterone. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12899-014-0009-x) contains supplementary material, which is available to authorized users.